A critique of translated (isiXhosa to English) sworn statements by the South African Police Service - Mvabaza, Aviwe (Rhodes University, Faculty of Humanities, School of Languages and Literatures, 2020)
The thesis provides a critique of sworn statement translations in the South African Police Service. The study is a mixed method study, which is rooted in Translation and Forensic Linguistics. It focuses on translations of two languages, IsiXhosa and English, an activity that was observed by the researcher at the Ndevana Police Station under the Buffalo City Municipality near King William's Town in the Eastern Cape Province. In addition to the data collection strategies, among others, the study also collected data through the use of questionnaires responded to by the Ndevana Location's community members. Furthermore, it used a method of consented interviews with the police officers. The main aim of these interviews was to unearth the police officers' views on whether they require Translators and Forensic Linguists to assist them. Moreover, the other data collection strategy used was the consented recordings of verbal statements made by complainants, facilitated by the capturing of translated written dockets after the reporting of an incident. The police officers involved and who were available in the precinct were Constables, Sergeants, Detectives, Warrant officers and the Captain. The study period was 90 days, and the data presented in the form of graphs is contained in the relevant upcoming chapters. The findings of the study were that there was indeed a need for Translators and/or Forensic Linguists in the precinct, as the statistics revealed, by both the police officers and the community members. An analysis of the transcribed material, the interviews with the police and the verbal statements made by the complainants written by the police were evidence of the need for Translators and Forensic Linguists by the South African Police Services.
Keywords: Forensic linguistics; Translators -- South Africa; Xhosa language -- Translating; Police administration -- South Africa